Multidisciplinary management of ventilator weaning and tracheostomies for COVID‐19 patients at a major NYC public hospital: A blueprint for other institutions. Issue 2 (1st March 2021) - Laitman, Benjamin M.; Filip, Peter; Gidumal, Sunder; Jolly, Joshpaul; Wasserman, Randi S.; Dilos, Barbara M.; Dave, Jasmine; Trosman, Samuel J.
Abstract : At the height of the coronavirus pandemic in New York City, at our hospital (NYC Health/Hospitals‐Elmhurst) 95% of inpatients tested positive for COVID‐19 and it operated at 500% surge ICU capacity—one of the greatest impacted centers in the nation. In the face of this we established a systematic multidisciplinary approach to manage ventilated ICU patients and select those appropriate for tracheostomy. Members from Pulmonary Critical Care, Anesthesiology, Surgery, Ethics, and Otolaryngology, created a protocolized way to assess all ICU patients in our hospital and, if deemed appropriate, help them towards weaning or tracheostomy and subsequent discharge. Given the climbing COVID numbers throughout the nation, and once again in NY, we believe sharing our protocol and brief outcomes will be very helpful for hospitals who are struggling with what we did, as it may serve as a blueprint for these institutions.